Response of Sorghum halepense demographic processes to plant density and rimsulfuron dose in maize. (26th April 2016) - Barroso, J; Maxwell, B D; Dorado, J; Andújar, D; San Martín, C; Fernández‐Quintanilla, C
Summary: In spatially heterogeneous weed infestations, variable dose technologies could be used to minimise herbicide use; high doses could be applied to reduce high‐density patches and low doses to maintain weed populations in low‐density portions of a field. To assess the potential short‐ and long‐term effects of variable herbicide dose and site‐specific management, the major weed demographic processes were described and parameterised in this study. Various doses of rimsulfuron (from 0 to 12.5 g a.i. ha −1 ) were applied to different densities of Sorghum halepense (0–100 plants m −2 ). Contrary to similar studies with other weed species, higher herbicide efficacy was not observed at low densities, suggesting that the same rimsulfuron dose should be applied regardless of the S. halepense density. The highest percentage of control was obtained with the full rimsulfuron dose. However, it did not guarantee a decrease of the infestation in the following season in the field areas where the initial S. halepense density was lower than 60 plants m −2 . Reduced doses of rimsulfuron to control S. halepense cannot be recommended based on our results.